Synthesis and characterization of pH responsive D-glucosamine based molecular gelators - Goyal, Navneet; Mangunuru, Hari P. R.; Parikh, Bargav; Shrestha, Sonu; Wang, Guijun (Beilstein Journal of Organic Chemistry, 2014)
Small molecular gelators are a class of compounds with potential applications for soft biomaterials. Low molecular weight hydrogelators are especially useful for exploring biomedical applications. Previously, we found that 4,6-O-benzylidene acetal protected D-glucose and D-glucosamine are well-suited as building blocks for the construction of low molecular weight gelators. To better understand the scope of D-glucosamine derivatives as gelators, we synthesized and screened a novel class of N-acetylglucosamine derivatives with a p-methoxybenzylidene acetal protective group. This modification did not exert a negative influence on the gelation. On the contrary, it actually enhanced the gelation tendency for many derivatives. The introduction of the additional methoxy group on the phenyl ring led to low molecular weight gelators with a higher pH responsiveness. The resulting gels were stable at neutral pH values but degraded in an acidic environment. The release profiles of naproxen from the pH responsive gels were also analyzed under acidic and neutral conditions. Our findings are useful for the design of novel triggered release self-assembling systems and can provide an insight into the influence of the the structure on gelation.
Keywords: glucosamine; hydrogelators; naproxen; organogelator; pH responsive; self-assembly